2014
DOI: 10.1088/0031-8949/89/12/125001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rotation on the growth rate of magnetogravitational instability of a viscoelastic medium

Abstract: In the present paper, we investigate the effect of rotation on the onset of gravitational collapse and the growth rate of magnetogravitational instability of a finitely electrically conducting viscoelastic medium under both strongly and weakly coupled plasma limits for transverse and longitudinal modes of wave propagation. A general dispersion relation, which is uniformly valid for both the transverse and longitudinal mode of wave propagation, is obtained using the normal mode analysis method. It is observed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…Equation (4.10) is the modified version of (16) in Dhiman & Sharma (2014) due to the neutral particles. In the hydrodynamic regime the above dispersion relation simplifies as …”
Section: Discussion Of the Dispersion Relationmentioning
confidence: 99%
See 3 more Smart Citations
“…Equation (4.10) is the modified version of (16) in Dhiman & Sharma (2014) due to the neutral particles. In the hydrodynamic regime the above dispersion relation simplifies as …”
Section: Discussion Of the Dispersion Relationmentioning
confidence: 99%
“…Therefore, looking to the importance of the Hall current and neutral particles in strongly coupled plasma systems, in the present work we have extended the study done by Argal et al. (2014) and Dhiman & Sharma (2014) by incorporating the effects of the Hall current and neutral particles. Argal et al.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Chandrasekhar (1961) used collision dominated magnetohydrodynamic (MHD) equations to study the effect of magnetic field and rotation on the gravitational instability and found that both magnetic field and rotation leave the Jeans wave number unaltered. The effect of rotation on the onset of gravitational collapse and the growth rate of magnetorotational instability of a finite electrically conducting viscoelastic medium under both strongly and weakly coupled plasma limits for transverse and longitudinal modes of wave propagation is investigated by Dhiman and Sharma (2014) and found that rotation reduces the growth rate of Jeans instability. It has been shown that the magnetorotational instability plays a crucial role in driving plasma turbulence in accretion disks and is believed to be responsible for angular momentum transport, which solves a long standing puzzle how the materials in the accretion disks fall inward to feed the stars or the black holes in the center (Velikhov, 1959;Chandrasekhar, 1960).…”
Section: Introductionmentioning
confidence: 99%